Role of radiotherapy in treatment of extramedullary relapse following total marrow and lymphoid irradiation in high-risk and/or relapsed/refractory acute leukemia - Colton Ladbury; Hemal Semwal; Hemal Semwal; Daniel Hong; Dongyun Yang; Claire Hao; Chunhui Han; An Liu; Guido Marcucci; Joseph Rosenthal; Susanta Hui; Amandeep Salhotra; et al. (Frontiers in Oncology, 2022)
BackgroundTotal Marrow and Lymphoid Irradiation (TMLI) is a promising component of the preparative regimen for hematopoietic cell transplantation in patients with high-risk acute myeloid leukemia (AML) and acute lymphoid leukemia (ALL). Extramedullary (EM) relapse after TMLI is comparable to TBI and non-TBI conditioning regimens. This study evaluates outcomes of patients treated with radiotherapy (RT) with EM relapse previously treated with TMLI.MethodsA retrospective analysis of five prospective TMLI trials was performed. TMLI targeted bones and major lymphoid tissues using image-guided tomotherapy, with total dose ranging from 12 to 20 Gy. EM recurrences were treated at the discretion of the hematologist and radiation oncologist using RT ± chemotherapy. Descriptive statistics and survival analysis were then performed on this cohort.ResultsIn total, 254 patients with refractory or relapsed AML or ALL were treated with TMLI at our institution. Twenty-one patients were identified as receiving at least one subsequent course of radiation. A total of 67 relapse sites (median=2 sites/patient, range=1-16) were treated. Eleven relapsed patients were initially treated with curative intent. Following the initial course of subsequent RT, 1-year, 3-year and 5-year estimates of OS were 47.6%, 32.7% and 16.3%, respectively. OS was significantly better in patients treated with curative intent, with median OS of 50.7 months vs 1.6 months (p<0.001). 1-year, 3-year and 5-year estimates of PFS were 23.8%, 14.3% and 14.3%, respectively. PFS was significantly better in patients treated with curative intent, with median PFS of 6.6 months vs 1.3 months (p<0.001). Following RT, 86.6% of the sites had durable local control.ConclusionsRT is an effective modality to treat EM relapse in patients with acute leukemia who relapse after HCT achieving high levels of local control. In patients with limited relapse amenable to curative intent, radiation confers favorable long-term survival. Radiation as salvage treatment for EM relapse after HCT warrants further evaluation.